Tourism Problems Policy in Labuan Bajo Using a Democratic Approach - Kuahaty, Johanis; Adoe, Yefri. C; Steven, Mitha K (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
Labuan Bajo, one of Indonesia's premier tourist destinations, faces significant challenges despite its growing popularity. Issues such as environmental degradation, economic inequality, and social conflict threaten the sustainability of tourism in the region. This study examines the application of democratic, participatory, and equitable approaches as potential solutions to these problems. The democratic approach emphasizes community involvement in decision-making processes to align tourism development with the needs and interests of local residents. The participatory approach encourages collaboration among stakeholders, including the government, private sector, and local communities, fostering sustainable tourism practices. Meanwhile, the equitable approach seeks to ensure a fair distribution of tourism benefits to prevent social conflicts and promote economic inclusivity. This research employs qualitative descriptive methods, utilizing literature reviews and multimedia sources to analyze tourism challenges and propose sustainable solutions. The findings reveal that incorporating democratic principles, such as establishing community tourism forums and supervisory bodies, can enhance local participation and environmental conservation. Additionally, community-based tourism initiatives provide greater economic benefits to local populations, reducing economic disparities. The results highlight the importance of a multi-stakeholder approach, where government, private entities, and local communities collaborate to address tourism-related challenges. The study concludes that a democratic framework, coupled with participatory and equitable strategies, is vital for achieving sustainable and inclusive tourism development in Labuan Bajo. These approaches not only safeguard environmental and cultural heritage but also ensure long-term economic growth that benefits all stakeholders.